Chinaʼs diplomacy and diaspora perceptions: Evidence from the Pacific region - Denghua Zhang (Asia & the Pacific Policy Studies, 2023)
Abstract Chinese diplomacy has been proactive under Xi Jinping and overseas Chinese are an important target. A better understanding of how overseas Chinese perceive Chinese diplomacy can increase our knowledge, but it is under‐studied in the literature. To fill part of this gap, this research focuses on the Pacific region where Chinaʼs activities have triggered growing geostrategic competition between traditional powers and China. Based on a survey of 182 ordinary overseas Chinese in Fiji and Tonga, this paper examines Chinese diasporaʼs perceptions of three aspects that are related to Chinaʼs diplomacy, including the Belt and Road Initiative, China‐Pacific bilateral relations, and old‐new Chinese issues. The survey reveals nuances in ordinary overseas Chinese views about Chinaʼs diplomacy, especially the concerns and apathy among some of them. It suggests that ordinary overseas Chinese support for Chinaʼs diplomacy is unlikely to grow substantially unless their views about this diplomacy become more positive.